THE INTERDEPENDENCE OF PLANNING, PROGRAMMING AND BUDGETING (Annual of the Faculty of Philosophy in Skopje, 2024)
Planning is a significant process function and counterpoises a very complex,dynamic and specific activity, which means that its subject consists of all forms of socialactivity, activities and life. Planning and programming are equally important to allentities regardless of their size and goals, as they all have experienced painful problemswith their planning efforts. Some emerge from the planning process itself, and somefrom the implementing procedure. Therefore the question arises: „How to help overcomefailures in planning from failures in implementation?” Hence, the management teamhas no choice regarding the question: “Do they want to plan or not?” The sole alternativeis to carry out the planning completely, pragmatically and systematically. Onthe other hand, programming connects planning with budgeting and execution, andcounterpoises a sort of rational assumption to “turn” plans from adopted plans into programs,that is, projects and activities across main accounting categories, in accordancewith the desired capabilities and priorities. The analysis of the entire matter processedin this paper is carried out in a very specific way through the prism of identifying notonly the problems related to planning, programming and budgeting, but also makinga scientific contribution to the foundation of this rather significant conditionality andinterdependence.
Keywords: planning; programming; budgeting; budget; budget process